UPAYA MENGHIDUPKAN BISNIS DENGAN INDRA MELALUI KEKUATAN AROMA DAN MUSIK - Sitepu, Rismawati Br; Pranoto, Henry Susanto; Dewi, Liliana; Soeparto, Wahyudi Henky; Suwangsih, Iwang (Universitas Panca Marga, 2025)
Consumer experience is an important element in creating loyalty and satisfaction amid business competition. This study explores the role of aroma and music in shaping a holistic consumer experience and how the combination of both can increase customer loyalty and engagement. Using a qualitative phenomenological approach, data were collected through in-depth interviews, participant observation, and documentation at businesses such as cafes, retail, spas, and hotels in Denpasar, Bali. The results show that aroma can evoke emotional memories, create a comfortable atmosphere, and prolong visits. Music affects mood, activity rhythm, and purchasing decisions. The combination of aroma and music creates a significant multisensory experience, increasing emotional attachment to the brand. This study expands the sensory marketing literature and provides practical guidance for business actors to design innovative marketing strategies in the tourism sector. Keywords: sensory marketing, consumer experience, aroma, music, customer loyalty.